The Kantian Critique of Psychoanalysis in Gilles Deleuze and Félix Guattari's Anti-Oedipus - Cherniavsky, Axel (2015)
"We cannot say they [psychoanalysts] are very jolly people; see the dead look they have, their stiff necks." The tone and register Gilles Deleuze and Félix Guattari used in Anti-Oedipus, published in 1972, caused an immediate public reaction: it was regarded as a fatal and massive criticism of psychoanalysis. Nevertheless, critique, in philosophy, at least since Kant, is used in certain very technical and precise senses. Almost half a century later, it may possibly be determined whether Anti-Oedipus is indeed a critique of psychoanalysis and, eventually, in which sense it is so. We believe that, technically, it is a delimitation of a Kantian sort, an evaluation of a Nietzschean kind and, finally, a divergence with a Deleuzian slant. In this occasion, we will try to demonstrate how it is a Kantian critique and we will discover that the object of this critique it is not psychoanalysis in general but something much more accurate.